A mixed method analysis of child sexual abuse and risky sexual behaviours among university students in Malaysia / Ashvini Jayapalan - Ashvini, Jayapalan (2018)
Many previous studies have showed that child sexual abuse (CSA) is associated with risky sexual behaviours (RSB). Additionally, there have been many misconceptions in understanding sexual abuse among the public. The lack of awareness and various views on perceiving sexual abuse among people of different ethnic minorities warrants in-depth understanding. The quantitative phase aimed to determine the prevalence of CSA experience and its association with unprotected sex during first sexual intercourse (RSB 1), unprotected sex throughout subsequent sexual intercourse (RSB 2) and multiple sexual partners (RSB 3). The purpose of the qualitative phase was to gain in-depth understanding of multi-ethnic perceptions on sexual abuse among female undergraduate students. The quantitative phase was a cross-sectional study conducted using an anonymous online survey. Respondents were undergraduate students from a public university in Malaysia. The qualitative phase involved focus group discussions among female undergraduate students from different ethnic minorities. In the quantitative study, a total of 1,650 undergraduate students responded. Only 1,383 (83.8%) responses were included in the analysis. The prevalence of CSA experience is 38.3% with rates being higher in females (41%, n=368) than males (33.2%, n=162). CSA experience was significantly associated with unprotected sex during first sexual intercourse (P=0.002) and multiple sexual partners (P=0.015) in the uni-variate analysis. In the multivariate logistic regression analysis, CSA experience was significantly associated with unprotected sex during first sexual intercourse (P=0.010). The likelihood of having unprotected sex during first sexual intercourse was higher in respondents who did not experience CSA (OR=2.56, 95%CI: 1.25-5.26). A total of 14 FGDs with a total of 75 students were conducted. Respondents from different ethnic groups perceived sexual iv abuse differently. Respondents perceived females, younger individuals, dress-code, good looks, soft and timid personalities, having lack of sexual knowledge, environmental factors and certain medical condition to be risk factors for sexual abuse victims. Sexual abuse perpetrators were perceived to be males, older individuals and most often a relative of the victim. Respondents also perceived that knowledge on sexual abuse amongst the community was insufficient and improper. CSA experience among university students is common in Malaysia and is associated with unprotected sex during first sexual intercourse (RSB 1). Many complaints on CSA in Malaysia do not lead to successful prosecution. This could largely be due to the weaknesses in the criminal justice system, police, law makers and child welfare groups. Furthermore, the Malaysian government does not publish data on CSA as it is protected under the Malaysia’s Official Act. Therefore, this problem needs to be addressed urgently and resources have to be made available for prevention against sexual abuse. Clinicians, who see patients with a history of CSA, should be aware of the relationship between CSA experience and risky sexual behaviours and be prepared to address the issue during their therapy. Additionally, sexual abuse is perceived differently among the ethnic groups in Malaysia. This shows that there is a need to strengthen sexual abuse prevention initiatives, awareness and sexual health promotion among young adults regardless of gender.